2015
DOI: 10.1007/s11012-015-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and sensitivity analysis of an axially moving beam

Abstract: The reliability and sensitivity analysis of an axially moving beam with simply supported boundary conditions are carried out. The equation of motion of the axially moving beam is established by applying the assumed mode method and Hamilton's principle. The critical divergence moving velocity is obtained from analyzing the stability of the kinetic equation of the beam. The uncertainties of the moving velocity, and the structural and material parameters of the beam are taken into account. The probability distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The superposition principle cannot be used for the nonlinear system, and the accurate probability distribution function of g ( B , x ) is impossible to calculate. 37 Therefore, the first four moments of g ( B , x ) can be used to describe the statistic properties of state function…”
Section: Dynamic Reliability Model Of Matched Bearingsmentioning
confidence: 99%
“…The superposition principle cannot be used for the nonlinear system, and the accurate probability distribution function of g ( B , x ) is impossible to calculate. 37 Therefore, the first four moments of g ( B , x ) can be used to describe the statistic properties of state function…”
Section: Dynamic Reliability Model Of Matched Bearingsmentioning
confidence: 99%
“…Pakdemirli and Ozkaya [2] and Yang et al [3] have examined the behavior of traveling continua that maintained constant velocity. This axial velocity is modeled as a harmonic function in the investigations carried out in [4][5][6][7][8][9][10][11][12][13][14][15][16] by considering different beam materials; damping terms; linear and nonlinear models of the beam. Oz [4], Pakdemirli and Oz [5], and Oz et al [6] used elastic beam material with simply supported boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Saksa et al [11] compared the dynamic characteristics of steel and paper adopting Poynting-Thomson model of axially accelerating viscoelastic beam. Yao and Yimin [12] carried out reliability and sensitivity analysis on traveling beam and concluded that the reliability of the moving system decreases when traveling velocity increases, the length of the beam increases for a particular speed, and it increases when the thickness of the beam increases and mass density decreases. Chakraborty and Mallik [13] made free and forced nonlinear vibration analysis of a traveling system using complex normal modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, due to initial, parametric, and external excitations, the generation of unwanted transverse vibrations may limit their applications. Therefore, the dynamic behaviors of such devices have been widely investigated by numerous scholars for the past decades and are still of interesting today [1][2][3][4][5][6][7][8][9][10]. Moreover, according to the demand of the actual engineering problems, some researchers have applied their theoretical results to design and optimize the axially moving structures [11,12].…”
Section: Introductionmentioning
confidence: 99%